“Rational” or “Intuitive”: Are Behavioral Biases Correlated Across Stock Market Investors? - Andrey Kudryavtsev; Gil Cohen; Shlomit Hon-Snir (Contemporary Economics, 2013)
Human judgments are systematically affected by various biases and distortions. The main goal of our study is to analyze the effects of five well-documented behavioral biases-namely, the disposition effect, herd behavior, availability heuristic, gambler's fallacy and hot hand fallacy-on the mechanisms of stock market decision making and, in particular, the correlations between the magnitudes of the biases in the cross-section of market investors. Employing an extensive online survey, we demonstrate that, on average, active capital market investors exhibit moderate degrees of behavioral biases. We then calculate the cross-sectional correlation coefficients between the biases and find that all of them are positive and highly significant for both professional and non-professional investors and for all categories of investors, as classified by their experience levels, genders, and ages. This finding suggests that an investor who is more inclined to employ a certain intuitive decision-making technique will most likely accept other techniques as well. Furthermore, we determine that the correlation coefficients between the biases are higher for more experienced investors and male investors, indicating that these categories of investors are likely to behave more consistently, or, in other words, are more likely to decide for themselves whether to rely on simplifying decision-making techniques in general or to reject all of them. Alternatively, this finding may suggest that these investors develop more sophisticated 'adaptive toolboxes', or collections of heuristics, and apply them more systematically.
Keywords: G01; D81; D84; G11; G14; G19; 330; availability heuristic; disposition effect; gambler's fallacy; herd behavior; hot hand fallacy